The Impact of labor Cost Control on the Performance and Risk of Listed Chinese Manufacturing Companies - He, Jiayi (2022)
Manufacturing is the backbone of China's economy, and labor-intensive industries account for a large proportion of the overall national economy. The good control of labor cost has a significant impact on the operation of enterprises. The scale of China's manufacturing industry is huge, and it is very difficult to promote the transformation of manufacturing industry. In recent years, China's labor and social security costs have increased, putting the manufacturing industry at a disadvantage in terms of labor price. And China's aging problem is gradually becoming prominent, which also means that manufacturing companies that rely on population advantages are facing difficulties. This paper will firstly classify and elaborate the literature related to labor cost control, corporate performance and risk. Additionally, this paper will analyze the current situation of labor cost control and the existence of risks of Chinese listed manufacturing companies in recent years. Then, hypotheses will be proposed and a relationship model will be constructed based on ten years of financial data of 542 Chinese listed manufacturing companies. Factor analysis of multiple indicators of independent variables will be conducted using SPSS and multiple regression analysis will be conducted using STATA. The main purpose of this paper is to investigate whether there is a significant relationship between labor cost control and healthy development of manufacturing companies. The main purpose of this study is to help Chinese manufacturing enterprises optimize their labor cost control system. At the same time, it will play a role in the healthy development of Chinese enterprises.